Step 3: Do a prenatal education in breastfeeding - Oscátegui Peña, Margarita Eli (2021)
Dear editor,After having read with interest the article "Factors associated with the level of knowledge about exclusive breastfeeding in first-time mothers attended by Teleconsulta - Instituto Nacional Materno Perinatal in 2020" by Vizquerra-Guevara P, et al. published in Volume 10 number 1 of the Peruvian Journal of Maternal Perinatal Research, which I consider a highly relevant study in the field of Obstetrics, especially in the field of Maternal Education; and taking into account that in 2019, according to ENDES, 65.6% of girls and boys under six months of age were breastfed1; I would like to outline some aspects that should be considered for further study.According to WHO and UNICEF, the ten steps towards happy breastfeeding (2018 revision), step 3 of prenatal information must be met - Explain to pregnant women and their families the importance of breastfeeding and its practice2 Currently in obstetric psychoprophylaxis sessions, R.M. N ° 361-2011 MINSA in session V provides educational activities on Breastfeeding, this guide is applicable in all establishments of the Ministry of Health nationwide3. On the other hand, RM No. 609-2014 / MINSA establishes the certification of establishments that are friends of the mother, girl and boy, considering that one of the evaluation criteria for certification is step 3 with the following standards:• Informational material on breastfeeding is available in prenatal care settings.• Medical records are records of breastfeeding counseling during prenatal care.• Pregnant women interviewed describe the risks of giving food supplements in the first six months: they describe the importance of early skin-to-skin contact and the importance of starting breastfeeding within the first hour after birth.• Pregnant women interviewed know the importance of breastfeeding and report that the staff helps them increase their own confidence and security.• Personnel interviewed who care for pregnant women show that they touch on key issues in verbal counseling during prenatal care4.In addition; RM No. 353-2016 / MINSA in step 3 establishes that if the health facility has at least one prenatal care service, it must offer breastfeeding counseling to pregnant women and their families about the importance of breastfeeding, risks of not breastfeeding, of providing substitutes, bottles, pacifiers, food supplements and materials for artificial feeding, the importance of breastfeeding during the first hour of your newborn's life, skin-to-skin contact, timely cord clamping umbilical, joint accommodation and breastfeeding on demand5.It is important to consider the MINSA's recommendations on criteria, parameters, and indicators that help us measure the level of knowledge about breastfeeding and the opening of a breastfeeding counseling office for pregnant women. The application of all the indicated information will serve as evidence of the work carried out by the institution and the achievement achieved.